CASHLESS POLICY AND E-PAYMENT SYSTEM IN NIGERIA: EFFICIENCY, PROSPECTS AND IMPLICATIONS - Damola Ajibike BAMIKOLE, Ph.D (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examined the efficiency, prospects, challenges and implications of cashless policy in Nigeria with respect to customers’ attitude towards the adoption of electronic banking services. Specifically focusing on selected six bank branches in Benin-city, Edo state and Port Harcourt, Rivers state respectively. Under the methods, the survey research design was adopted whereby 100 customers were conveniently sampled from the customers of the selected deposit money banks. The instrument for data collection was the questionnaire which was titled “Bank Customers’ Attitude Towards Adoption of E-Banking Services Questionnaire” (BCATAEBSQ) and was divided into three parts. The data received from the respondents were analyzed using SPSS for windows version 23. Mean and standard deviation were used to analyze the data. From the results of the analysis, it was revealed that all the sampled banks offer various electronic banking services to their customers, and that customers exhibit positive attitude towards the adoption of electronic banking services offered by their banks which brought about cashless policy; also, the extent to which customers’ attitude influences the adoption of electronic banking services in Nigeria is high. It was recommended that since customers display positive attitude towards the adoption of e-banking services, banking organizations should continually see the need to spice up these services with low fees in order not to dissuade them from continuous utilization. Bank employees should also be updated always on more productive utilization of these software\packages.